Charge transfer complex formation between organic interlayers drives light-soaking in large area perovskite solar cells - Henderson,C; Luke,J; Bicalho,I; Correa,L; Yang,E; Rimmele,M; Demetriou,H; Heutz,S; Gasparini,N; Heeney,M; Bagnis,D; Kim,JS (Energy and Environmental Science, 2023)
Light soaking (LS) is a well-known but poorly understood phenomenon in perovskite solar cells (PSCs) which significantly affects device efficiency and stability. LS is greatly reduced in large-area inverted PSCs when a PC61BM electron transport layer (ETL) is replaced with C60, where the ETL is commonly in contact with a thin bathocuproine (BCP) interlayer. Herein, we identify the key molecular origins of this LS effect using a combination of surface photovoltage, ambient photoemission spectroscopy, Raman spectroscopy, integrated with density functional theory simulations. We find that BCP forms a photoinduced charge-transfer (CT) complex with both C60 and PC61BM. The C60/BCP complex accelerates C60 dimer formation, leading to a favourable cascading energetic landscape for electron extraction and reduced recombination loss. In contrast, the PC61BM/BCP complex suppresses PC61BM dimer formation, meaning that PC61BM dimerisation is not the cause of LS. Instead, it is the slow light-induced formation of the PC61BM/BCP CT complex itself, and the new energetic transport levels associated with it, which cause the much slower and stronger LS effect of PC61BM based PSCs. These findings provide key understanding of photoinduced ETL/BCP interactions and their impact on the LS effect in PSCs.